2020
DOI: 10.1016/j.psj.2020.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of on-farm and traditional hatching on welfare, health, and performance of broiler chickens

Abstract: In on-farm hatching systems, eggs that have been incubated for 18 D are transported to the broiler farm. After hatching around day 21, the chicks have immediate access to feed and water. By contrast, traditionally hatched chicks are in early life exposed to dust and pathogens in the hatcher, handling procedures, and transport and remain without feed and water until they have arrived on the farm 1 to 3 D after hatching. We compared welfare and performance of on-farm hatched ( OH ) and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
63
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(88 citation statements)
references
References 35 publications
19
63
6
Order By: Relevance
“…Other indicators of day-old chicken quality, that is, navel condition and red hocks ( van de Ven et al., 2012 ), were worse for OH chickens compared with the other treatments. This is in accordance with previous findings ( de Jong et al., 2019 , 2020 ), and it could be because of suboptimal or more variation in hatching conditions at the broiler farm. It has been found that a high incubation temperature and consequently larger residual yolk can be related to a worse navel quality, although other factors seem to be related as well ( Molenaar et al., 2010 ; Nangsuay et al., 2016 ; Van den Brand et al., 2019 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Other indicators of day-old chicken quality, that is, navel condition and red hocks ( van de Ven et al., 2012 ), were worse for OH chickens compared with the other treatments. This is in accordance with previous findings ( de Jong et al., 2019 , 2020 ), and it could be because of suboptimal or more variation in hatching conditions at the broiler farm. It has been found that a high incubation temperature and consequently larger residual yolk can be related to a worse navel quality, although other factors seem to be related as well ( Molenaar et al., 2010 ; Nangsuay et al., 2016 ; Van den Brand et al., 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous results ( de Jong et al., 2019 , 2020 ), day-old OH and HF chickens were heavier than HH chickens, likely because they could eat and drink immediately after hatching ( van de Ven et al., 2009 ). In accordance with this, day-old chickens were longer for HF and OH than HH, suggesting a better day-old chicken quality and possibly also a better posthatch performance, although the relationship between chicken length and later life performance does not always seem to be very strong ( Willemsen et al., 2008 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations